A clinical case report on transcranial low-intensity focused ultrasound neuromodulation for central post-stroke pain - He, Sijin; Luo, Kaixuan; Li, Xiang; Duan, Jiajia; Ding, Lei; Chen, Moxian; Xu, Xuan; Sun, Xianghua; Ao, Lijuan; Feng, Xiangjun (Frontiers in Neuroscience, 2025)
Central post-stroke pain (CPSP) manifests as persistent or intermittent pain following cerebral infarction or hemorrhage and is described as “one of the most agonizing, disabling, and refractory pain syndromes.” Its treatment represents a significant clinical challenge. In this case, we used transcranial low-intensity focused ultrasound (tLIFU), an emerging non-invasive neuromodulation approach distinct from pharmacological and traditional neuromodulation methods, to treat CPSP patients, achieving satisfactory outcomes. This approach may inspire new perspectives on innovative pain management. A 66-year-old male veteran suffered long-term CPSP, with unsatisfactory pain relief from previous paregoric interventions, including transcranial magnetic stimulation (TMS). Blood oxygenation level-dependent functional magnetic resonance imaging (BOLD-fMRI) revealed abnormal activity in a region of interest (ROI) that responded to analgesic medication adjustments. This ROI was anatomically consistent with the cingulum bundle. Given this finding, we used tLIFU to demonstrate deep stimulation of the ROI. Remarkable pain reduction was observed after 1 week of tLIFU neuromodulation, allowing for a slight tapering of the gabapentin dose. The analgesic effects of tLIFU were sustained throughout a 5-month follow-up period, with no adverse events reported. Since day 120, the patient has remained off analgesic medications, and at the 150-day follow-up, BOLD-fMRI revealed a normalized activity pattern in the region of interest (ROI). Additionally, significant clinical improvement was noted in the patient’s emotional state. This case report highlights the potential of tLIFU technology to expand therapeutic options in clinical pain management. Exploratory research into the clinical efficacy and the underlying mechanisms of tLIFU in pain treatment may contribute to a deeper understanding of pain pathogenesis and support the development of novel therapeutic strategies.